Challenges to the implementation of telemedicine in abortion care for victims of sexual violence in Brazil - Galli, Beatriz; Dillon, Jina (Frontiers in Global Women's Health, 2022)
The article focuses the recent dynamics resulting from state institutions adding more legal and regulatory barriers to abortion care access, particularly against the use of telemedicine for sexual violence victims in Brazil. It presents a case study from a lawsuit targeting a pioneer public health service on the city of Uberlandia to ban telemedicine in abortion care. The case study highlights human rights violations of women’s right to health as well as the recent threats to the right to safe legal abortion care. It also provides legal arguments—based on scientific evidence and international human rights standards—that support the use of telemedicine for abortion care.